Effects of tip gap on transonic turbine blade heat transfer characteristics with pressure side film cooling. (15th May 2022) - Collopy, Hallie; Ligrani, Phillip M.; Xu, Hongzhou; Fox, Michael
Highlights: Local, spatially-resolved and line-averaged distributions of surface adiabatic film cooling effectiveness and surface heat transfer coefficient ratios are provided for a transonic turbine blade tip. Blade includes a squealer rim, and a single row of film cooling holes is located on the pressure-side of the blade very near to the blade tip Improved surface thermal protection on the squealer tip surface, from pressure side film cooling, is often present with a smaller tip gap Effectiveness data for the suction side rim with the smaller tip gap, show complicated variations as blowing ratio changes. Local surface heat transfer coefficient data deviations are due to locally augmented mixing and shear, and increased turbulent transport from the advective presence of the film coolant Local surface heat transfer coefficient variations are due to a horseshoe-shaped vortex structure, whichforms around each film cooling concentration. Abstract: Investigated are local, spatially-resolved and line-averaged distributions of surface adiabatic film cooling effectiveness and surface heat transfer coefficient ratios for a transonic turbine blade tip. The tip contains a squealer rim, and a single row of film cooling holes is located on the pressure-side of the blade very near to the blade tip. A two-dimensional linear cascade, with four flow passages and five complete blades, is utilized for the investigation. Associated data are provided for different film cooling flow conditions for two different tip gaps, which correspond to 1.16 and 0.66% of true blade span. Experimentally-measured, spatially-resolved surface data demonstrate that improved surface thermal protection on the squealer tip surface, from pressure side film cooling, is often present with a smaller tip gap. Such a conclusion is illustrated by heat transfer coefficient values at many surface locations which are generally lower, and by adiabatic film cooling effectiveness magnitudes which are often substantially larger for the smaller tip gap, relative to values associated with the larger tip gap. Associated effectiveness values, along the upper pressure side, vary in a significant manner as blowing ratio changes. Along the tip region of the blade, for both tip gap values, line-averaged adiabatic film cooling effectiveness generally increases with increasing blowing ratio for the pressure side rim. Effectiveness data for the suction side rim with the smaller tip gap, show more complicated variations as blowing ratio changes. Heat transfer coefficient data along the squealer tip surface and on the upper pressure side of the blade surface generally have variations which are similar to the baseline blade with no film cooling for many surface locations. The local deviations, which are present, are due to locally augmented mixing and shear, and increased turbulent transport from the advective presence of the film coolant.